TRANSFORMATIVE EDUCATIONAL: EXPLORING THE CREATIVE POTENTIAL OF ELEMENTARY SCHOOL - Pastika Sandi, Anggun; Marini, Arita; Zakiah, Linda (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research aims to explore transformative education as an effort to unlock children's creativity potential in elementary schools. Creative potential is one aspect that can be examined through transformative education. The research method used is qualitative descriptive with a library research approach. The results indicate that one aspect of transformative education's objectives is to shape individuals who are skilled, creative, and independent, ready to face the challenges of modern development, aligning with the vision and mission of National Education. One outcome of transformative learning is the creativity and intelligent actions of the millennial generation in the interaction process of learning, which can enhance self-confidence in interacting with the environment. The learning process also focuses on developing students' creativity. Therefore, the integration of transformative education and creativity development must be prioritized in the education system to create a better future generation.